- #1

Monoxdifly

MHB

- 284

- 0

a. \(\displaystyle x^2+y^2-3x-6y=0\)

b. \(\displaystyle x^2+y^2-12x-6y=0\)

c. \(\displaystyle x^2+y^2+6x+12y-108=0\)

d. \(\displaystyle x^2+y^2+12x+6y-72=0\)

e. \(\displaystyle x^2+y^2-6x-12y+36=0\)

Since the center (a, b) lays in the line y = 2x then b = 2a.

\(\displaystyle (x-a)^2+(y-b)^2=r^2\)

\(\displaystyle (0-a)^2+(6-b)^2=r^2\)

\(\displaystyle (-a)^2+(6-2a)^2=r^2\)

\(\displaystyle a^2+36-24a+4a^2=r^2\)

\(\displaystyle 5a^2-24a+36=r^2\)

What should I do after this?